THEORETICAL BASIS FOR THE DEVELOPMENT OF RESOURCE POTENTIAL OF RAILWAY TRANSPORT ENTERPRISES - Korin , Myroslava; Lanovyi , Oleksii (Collection of scientific papers «ΛΌГOΣ», 2023)
The ability of railway transport enterprises to provide high-quality transport services and sustainably withstand competition in the transportation market depends on the quantity and quality characteristics of their resource potential, the availability of effective mechanisms for its use and mobilization. The complexity of the economic environment of railway transport enterprises and their course towards digital restructuring of the industry requires the introduction of effective approaches to increasing their resource potential to support the efficiency of modernization processes. The specifics of the activities of railway transport enterprises also leave their mark on the resource potential. A distinctive feature of the resource potential of railway transport enterprises is as follows: